Pengaruh Financial Pressure, Sistem Pengendalian Internal Dan Integritas Terhadap Kecenderungan Kecurangan (Fraud) Akuntansi Pada Lembaga Perkreditan Desa (LPD) Se-Kecamatan Kintamani Bangli - Ni Putu Rismayanti; Ni Putu Ayu Kusumawati; Putu Nuniek Hutnaleontina (UNHI Press, 2023)
A Propensity to Defraud Accounting fraud is the intentional misrepresentation of a company's financial position for the purpose of gaining an advantage in a business transaction. One of the precursors to the appearance of corrupt criminal acts is the prevalence of accounting fraud. The purpose of this research is to identify the relationship between financial stress, internal control systems, and honesty as they relate to the propensity for accounting fraud at Village Credit Institutions (LPD) in the Kintamani Bangli District. The participants included all current and former employees from the 57 LPDs in the Kintamani District. Purposive sampling was used to select the study's sample size of 171 participants, and the results were analyzed with multiple linear regression.Findings from this research show that financial stress significantly increases the likelihood of accounting fraud. Accounting fraud trends are impacted negatively by the presence of an effective internal control system. Integrity reduces the likelihood of accounting fraud. Based on the findings, it is hoped that in the future employees of Village Credit Institutions (LPD) in the Kintamani Bangli sub-district will be better able to manage their finances, avoid excessive debt, and live comfortably despite fluctuating incomes. Obviously, this will discourage any employee who might otherwise be tempted to commit fraud.